Optimization of Contractor’s Cash Flow Based on Subcontractor’s Payment Management Plans - Ghali, Helen (AUC Knowledge Fountain, 2023)
In many counties, the construction industry relies heavily on outsourcing packages to execute their projects and expand their businesses to fit in the diverse market. Such extensive integration of outsourced subcontractors is becoming an influential factor in contractors' cash flow management. Accordingly, subcontractors’ price selection and their respective payment plans are important phenomena and pivotal components for the well-being of the contractor’s cash flow. Cash flow management is considered one of the most critical areas analyzed by contractors when getting into a project. Contractor’s cash flow is built from a pool of interrelated information depending on subcontractors, suppliers trade credit arrangement with the contractor, owner payment terms and the project schedule. Various researchers have developed models to optimize contractors’ cash flow financing costs however considering that activities are self-executed and neglect the subcontractor’s credit arrangements. Accordingly, limited research is available on a near-real presentation of a contractor’s cash flow model including the different subcontracted packages with their payment conditions. Also, during project procurement of subcontracting packages, contractors are usually presented with different subcontracting prices and payment conditions in which the contractor base its selection on the least price with little investigation of the effect on the contractor’s cash flow. Accordingly, the purpose of this work is to study the contractor’s cash flow with respect to the owner and subcontractor’s payment management plans. A model structure is developed to provide contractors with a cash flow profile that considers subcontracting of packages with variable payment conditions as advance payment, payment frequency, payment lag and retention percentages. The model is also used as a decision tool to assist contractors in evaluating different subcontractors’ commercial offers and their payment conditions and select the optimum subcontracting plan that minimizes the contractor’s negative cash flow and reduces its financing requirements. It helps contractors in selecting the optimum subcontracting combinations to reduce the required liquidity and increase contractor’s profits. The model is built using Microsoft Excel and a VBA user customized function to allow for dynamic integration of subcontractor’s payment conditions into contractor’s cash-out graph. Two different objective functions are considered namely maximizing the highest negative overdraft value and maximizing net present worth of the contractor’s net cash flow values. The results from the two objective functions are analyzed and the performance of both has shown potential uses in devising an optimum combination. The model is first developed on a prototype project which encompasses subcontracted activities and self-performed works and the prototype results of the two objective functions are discussed, then a sensitivity analysis is carried out on contractor’s cash flow objective functions when varying the subcontractor’s payment conditions. Finally, the model is validated on a full-scale project and the outcomes and results of the model are analyzed.